(untitled) (Actual Problems of Mind, 2016)
The paper presents a revision of a problem of ego-identity in a context of the linguistic dimensions of the classical (Cartesian) and non-classical philosophical traditions; it is claimed that the integrative-projective characteristics of a language have no sense beyond the framework of the language itself. The authors makes an attempt to revitalize a mono-centric model (on the basis of a Jungian analytic paradigm).